12
cara gimana kok bisa ketemu 12
f(x) = mx + n
f(-1) = -1m + n = 2
f(2) = 2m + n = 11 -
-3m = -9
m = 3

-1m + n = 2
-3 + n = 2
n = 5

f(4) = 4.(3) + 5
= 12 + 5
= 17
maksudya 17 hehehe

Jawabanmu

2014-04-09T07:59:30+07:00
F(x) = mx + n
f(-1) = -1m + n = 2
f(2) =  2m + n = 11 -
          -3m     = -9
             m     = 3

-1m + n = 2
-3 + n    = 2
       n    = 5

f(4) = 4.(-1) + 5
     = (-4) + 5
     = -1

bener gak?
ohiya salah. harusnya f(4) = 4. (3) + 5
2014-04-09T08:07:45+07:00
F(-1) = -1 m + n = 2
f(2) = 2m + n = 11

f(-1) =( -1m + n =2 ) -2
f(-1) = 2m -2n = -4

f(2) = 2m + n = 11
f(-1)= 2m -2n = -4 -
               3n = 15
                 n = 5

2m + n = 11
2m + 5 = 11
       2m = 11-5
       2m = 6
         m = 3

f(4) = 3(4) + 5 = 12 + 5 = 17
2 3 2